Lemahnya Pengendalian Internal Berdamapak Terjadi Mark Up Biaya Pengawalan PT ALRSY - Martias, Andi (Universitas Bina Sarana Informatika, 2019)
Internal audit can be interpreted as an audit and assessment activity in a company as a whole, which aims to help all levels of management in carrying out their responsibilities effectively through the provision of useful advice to improve performance at each level of management. The method of this research is a qualitative approach. To ensure the independence, objectivity and quality of the process, an internal auditor is needed as a facilitator in the process which will also independently report the results to the company's management and also as a basis for control. As a logistics company, companies often receive orders to ship items for project needs such as heavy equipment, spare parts, etc., to ensure that there are no disturbances on the road, the company usually requests police escort services. From the police there is no official tariff to be paid because of its assistance. Because there is no official tariff, it causes irregularities in practice. This study analyzes the weaknesses that occur due to a lack of internal controls. . From the description and analysis discussed earlier, conclusions can be taken that must be considered to avoid the occurrence of fraud cases again is the nature of prudence (overconfidence in colleagues, communication systems that have not been effective, low honesty, integrity and loyalty of employees). Keywords: Internal Control.Internal Auditing,Fraud